2016
DOI: 10.1007/s11118-016-9569-7
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Dirichlet Problem for 𝓐 $\mathcal {A}$ -Harmonic Functions on Manifolds with Pinched Curvature

Abstract: Abstract. We study the asymptotic Dirichlet problem for A-harmonic functions on a Cartan-Hadamard manifold whose radial sectional curvatures outside a compact set satisfy an upper boundand a pointwise pinching conditionfor some constants ε > 0 and C K ≥ 1, where P and P are any 2-dimensional subspaces of TxM containing the (radial) vector ∇r(x) and r(x) = d(o, x) is the distance to a fixed point o ∈ M . We solve the asymptotic Dirichlet problem with any continuous boundary data f ∈ C(∂∞M ).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, the class of manifolds admitting nontrivial solutions of some elliptic equations is wide. For example, conditions ensuring the solvability of the Dirichlet problem with continuous boundary conditions "at infinity" for several noncompact manifolds has been found in many papers (see, e. g., [1,5,7,10,15]).…”
Section: Introductionmentioning
confidence: 99%
“…However, the class of manifolds admitting nontrivial solutions of some elliptic equations is wide. For example, conditions ensuring the solvability of the Dirichlet problem with continuous boundary conditions "at infinity" for several noncompact manifolds has been found in many papers (see, e. g., [1,5,7,10,15]).…”
Section: Introductionmentioning
confidence: 99%
“…Recently the asymptotic Dirichlet problem for minimal graph, f -minimal graph, p-harmonic and A-harmonic equations has been studied for example in [22], [30], [31], [7], [21], [8], [6], [5], and [17], where the existence of solutions was studied under various curvature assumptions and via different methods. In [8] the existence of solutions to the minimal graph equation and to the A-harmonic equation was proved in dimensions n ≥ 3 under curvature assumptions − log r(x)) 2ε r(x) 2 ≤ K(P x ) ≤ − 1 + ε r(x) 2 log r(x)…”
Section: Introductionmentioning
confidence: 99%
“…, (1.3) where ε >ε > 0, P x ⊂ T x M is a 2-dimensional subspace, x ∈ M \ B(o, R 0 ), and r(x) = d(o, x) is the distance to a fixed point o ∈ M . In [17] it was shown that in the case of A-harmonic functions the curvature lower bound can be replaced by a so-called pinching condition…”
Section: Introductionmentioning
confidence: 99%